Broadcasters’ expertise and consumers’ purchase intention: The roles of consumer trust and platform reputation - Li, Jie; Zheng, Ruyi; Sun, Haiqin; Lu, Jiaoying; Ma, Wenbo (Frontiers in Psychology, 2022)
Following the outbreak of COVID-19, farmer-assisted live streaming has become a hot topic in China. In this article, we explore the ways in which broadcaster and platform characteristics jointly influence consumers’ purchase intention. To examine our hypotheses, we distributed questionnaires to 261 Chinese consumers who viewed farmer-assisted live streaming. Correlational analyses, regression analyses, and confirmatory factor analyses were conducted to examine our hypotheses. The results show that broadcasters’ expertise is positively related to consumer trust and that platform reputation moderates this relationship. In addition, consumer trust mediates the positive relationship between broadcasters’ expertise and consumer purchase intention. Furthermore, the theoretical and practical implications of these findings are discussed.